(3GdfRgI GdSfjI ajeG jWdH ef CNHGQ Gdedhc hNdaGA GdOjGQ GdeUQjIs - (3YHO GdYRjR Hf YeQ Hf eMeO, YR GdOjf , CHh GdNjQ , GdTgjQ HGHf agO,J (B920 (3g` s
(3ChdgG (B:s
(3GdMeO ddg NGdb cd TF hdg GdUaGJ GdCRdjI hHYO agPg fRgI SfjI eZfjI eeG jWdH ef CNHGQ GdNdaGA hGdedhc GdeUQjI hLYdJgG ddNRGFf GdYGdjI s
(3BNQgG (B:s
(3Jhdi ehdGfG GdebGe GdTja GdSdWGf Gdedc GdCTQa CHh GdfUQ bGjJHGi GdeMehOi CWGd Gddg JYGdi eOJg hNJe dfG hdge HGdNHQ ai GdOfjG hGdBNQI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B24s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B254s
(3eUOQ GbJfGA GdCUd (B:s
(3ESchQjGd (B(1708/2) s
Keywords: (3GdJGQjNs